SOIL ENZYMATIC ACTIVITY OF UROCHLOA PASTURES MANAGED UNDER DIFFERENT FORAGE ALLOWANCES - Janusckiewicz, E. R. [UNESP]; Raposo, E. [UNESP]; Martins, B. M. P. R. [UNESP]; Magalhaes, M. A.; Panosso, A. R.; Melo, G. M. P.; Ruggieri, A. C. [UNESP] (Inst Zootecnia, 2019)
Soil enzymatic activity reflects the activity microorganisms that decompose the organic matter and release nutrients into the soil that can be used by plants. The objective of this study was to evaluate soil enzymatic activity in Urochloa cultivar pastures managed under forage allowances of 4, 7, 10 and 13 kg dry matter/100 kg body weight. The grazing method adopted was mob-stocking, with four grazing cycles (between December 2008 and February 2009). Soil sampling was performed in June 2009 for better characterization since the mineralization of soil organic matter is a long-term process. Thus, the dates of soil sampling for analysis are reported as evaluation days and not as grazing: 1 (December 17 to 20, 2008), 21 (January 7 to 10, 2009), 42 (January 28 to 31, 2009), 63 (February 18 to 21, 2009), 183 (June 18 to 20, 2009). The soil enzymatic activity of dehydrogenase, protease, arylsulfatase, and cellulase was evaluated. The experimental design was completely randomized, with three replications per forage allowance. Analysis of variance and Tukey's test at the 5% probability level were applied to compare means using the R statistical program. The analyses were performed individually for each cultivar. Overall, in pastures of the three cultivars studied, dehydrogenase activity was higher (P<0.05) on day 63 and protease on the last day of evaluation. The experimental period implied changes in the activity of arylsulfatase and cellulase according to forage allowance, but without a defined pattern. Forage allowances exerted an effect on the activity of the enzymes throughout the evaluation period, but there was no defined pattern. Cyclic oscillations in the activity of these enzymes were observed. The forage allowances studied affected the soil enzymatic activity of dehydrogenase, protease, arylsulfatase and cellulase in Urochloa pastures of the Marandu, Xaraes and Mulato varieties, but no pattern was found in this activity. A longer study period is necessary to identify more specific effects of forage allowance on soil enzymatic activity in Urochloa pastures.
Keywords: arylsulfatase; cellulase; dehydrogenase; protease; soil moisture